PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, KECERDASAN SPIRITUAL, DAN KECERDASAN SOSIAL TERHADAP PEMAHAMAN AKUNTANSI (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2019)
The purpose of this research is to determine the effect of emotional intelligence, intellectual intelligence, spiritual intelligence and social intelligence on understanding accounting. This study is an empirical study conducted on students of accounting study program, islamic university of kuantan singingi. The design of this study is causal associative research (causal relations). the data used in this study are quantitative data. the population and sample in this study were students of accounting study program in the seventh semester of the year 2014 Islamic university of kuantan singingi. Sampling is done through purposive sampling. data obtained through questionnaires. Data analysis using multiple linear regresion and independent sample T test with the help of SPSS version 20.00 software. The results showed that emotional intelligence had a significant effect on accounting understanding with a significant P of 0.0005, intellectual intelligence had a significant effect on accounting understanding with a significant p of 0.000, spiritual intelligence had a significant effect on accounting understanding with a significant 0.038. and social intelligence has a significant effect on accounting understanding with a significant p of 0.042.